Semimetal Bismuth‐Enhanced Light Adsorption and Interface Charge Transfer in Bi@BiVO4. Issue 19 (18th May 2020) - Zhai, S.; Yang, X.; Liang, S.; Hao, W.; Teng, F.
Abstract: In this work, a simple, mild glucose‐reduction method is developed to synthesize the uniform bismuth‐loaded BiVO4 (Bi@BiVO4 ) nanospheres. Compared with BiVO4, the photocurrent of 0.1Bi@BiVO4 increases by 45 times, suggesting an obviously improved charge transfer and separation efficiency; its negative surface photovoltage (SPV) signal becomes much stronger, indicating that more generated carriers migrate to the irradiation surface of Bi@BiVO4 . Compared with BiVO4 nanospheres, the visible‐light activity of Bi@BiVO4 increasesby 1.3 times for the methylene blue (MB) degradation. Surface plasma resonance (SPR) of semimetal bismuth, Schottky junction and the increased surface area mainly attributed to the enhanced photoactivity of Bi@BiVO4 . The adopted method is simple, safe, which could be promising for mass production. Abstract : A simple glucose‐reduction method is developed to synthesize the uniform bismuth‐loaded BiVO4 (Bi@BiVO4 ) nanospheres, which shows a 2.3 times visible‐light activity as high as that of BiVO4 for the degradation of methylene blue (MB).